PENGEMBANGAN APLIKASI PENGENALAN PROFESI BERBASIS AUGMENTED REALITY BAGI SISWA TAMAN KANAK-KANAK - Fransiska Pasinia Bele Bau; Siprianus Septian Manek; Patricia Gertudis Manek; Budiman Baso (LPPM Universitas Abdurrab, 2026)
The profession introduction learning process at TK Negeri Dharma Wanita Kefamenanu is currently still conventional and teacher-centered, using images and videos as media, which makes children tend to be passive and less actively engaged. This study aims to produce a profession introduction application based on Augmented Reality (AR) that is suitable for the characteristics of kindergarten students. The development followed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with implementation using Unity and Vuforia. The application displays 3D objects of thirteen professions equipped with animations, audio, and a letter-arranging game. Functional testing (Black Box Testing) and User Acceptance Testing (UAT) were conducted. The test results showed that all features functioned properly and the UAT average score reached 93.02% in the very good category. The conclusion of this study is that the ProfesiKu AR application was successfully developed and is feasible to be used as a learning medium for profession introduction for kindergarten students.